Multidisciplinary standards of care and recent progress in pancreatic ductal adenocarcinoma. (19th July 2020) - Grossberg, Aaron J.; Chu, Linda C.; Deig, Christopher R.; Fishman, Eliot K.; Hwang, William L.; Maitra, Anirban; Marks, Daniel L.; Mehta, Arnav; Nabavizadeh, Nima; Simeone, Diane M.; Weekes, Colin D.; Thomas, Charles R.
Abstract: Despite tremendous gains in the molecular understanding of exocrine pancreatic cancer, the prognosis for this disease remains very poor, largely because of delayed disease detection and limited effectiveness of systemic therapies. Both incidence rates and mortality rates for pancreatic cancer have increased during the past decade, in contrast to most other solid tumor types. Recent improvements in multimodality care have substantially improved overall survival, local control, and metastasis‐free survival for patients who have localized tumors that are amenable to surgical resection. The widening gap in prognosis between patients with resectable and unresectable or metastatic disease reinforces the importance of detecting pancreatic cancer sooner to improve outcomes. Furthermore, the developing use of therapies that target tumor‐specific molecular vulnerabilities may offer improved disease control for patients with advanced disease. Finally, the substantial morbidity associated with pancreatic cancer, including wasting, fatigue, and pain, remains an under‐addressed component of this disease, which powerfully affects quality of life and limits tolerance to aggressive therapies. In this article, the authors review the current multidisciplinary standards of care in pancreatic cancer with a focus on emerging concepts in pancreatic cancer detection, precision therapy, and survivorship.